Предмет: Алгебра, автор: vladkozimuratov5

Плиз даю 100 Балов помогите ​

Приложения:

Ответы

Автор ответа: сок111213
0

( \frac{ {b}^{2}  + 16}{ {b}^{2} - 16 }  +  \frac{b}{b + 4}  +  \frac{b}{4 - b} ) \div  \frac{ {b}^{2}  - 4b}{(b + 4) {}^{2} }  =  \\  = (  \frac{ {b}^{2}  + 16}{ ({b} - 4)(b + 4) }  +  \frac{b}{b + 4}   -   \frac{b}{b - 4} ) \div  \frac{ {b}(b  - 4)}{(b + 4) {}^{2} }  = \\  =  \frac{ {b}^{2} + 16 + b(b - 4) - b (b + 4)}{(b - 4)(b + 4)}  \times  \frac{(b + 4) {}^{2} }{b(b - 4)}  =  \\  =  \frac{ {b}^{2} + 16 + b {}^{2} - 4b -  {b}^{2}  - 4b  }{(b - 4)}  \times  \frac{b + 4}{b(b - 4)}  =  \\  =  \frac{ {b}^{2}  - 8b + 16}{b - 4}  \times  \frac{b + 4}{b(b - 4)}  =  \frac{(b - 4) {}^{2} }{b -  4}  \times  \frac{b + 4}{b(b - 4)}  =  \\  =  \frac{b + 4}{b}

Похожие вопросы
Предмет: Другие предметы, автор: fokichevegor8